Developing Students' 4C Skills (Communication, Collaboration, Creativity, Critical Thinking): Psychomotor Assessment Techniques in Visionary Schools - Brata, Diah Puji Nali; Utomo, Edy Setiyo; Farhan, Ahmad (QALAMUNA: Jurnal Pendidikan, Sosial, dan Agama, 2023)
The purpose of this study was to describe the development of 4C skills (Communication, Collaboration, Creativity, and Critical Thinking) through psychomotor assessment techniques in three visionary schools, namely SMPN 1 Gresik, SMPN 2 Mojokerto, and SMPN 4 Jombang. This research used a descriptive qualitative method. The research instruments consisted of interview sheets and observation guidelines. The research indicator refers to activities how as observation, practice, project, and produce products. The technique of data collection was through the interview and learning observation. Triangulation of research data used the source and technique. The research used technique analysis in data reduction, data categorization, data presentation, and data conclusion. The result showed that the development of 4C skills (Communication, Collaboration, Creativity, and Critical Thinking) done by teachers consisted of observation with 11 activities, practice with 17 activities, product with 25 activities, and project with 13 activities) where each indicator was done in 6 stages of activities, namely stimulus, planning, action, evaluation, monitoring, and follow-up activities. Besides, the technique of psychomotor assessment used in learning inside and outside class was rubric, anecdote, and checklist.